Sensors and Control Systems in Manufacturing, Second Edition - Soloman, Sabrie (McGraw-Hill Education, 2010)
The second edition of Sensors and Control Systems in Manufacturing fully explains the technical aspects of the latest senor technologies, showing how to select and install simple, affordable sensors to maximize productivity and minimize production errors. This ?one-stop" guide offers you hands-on instruction on integrating various sensors with appropriate contro lmeans throughout manufacturing operations. The book presents state-of-the-art information on traditional sensors, laser sensors, LED sensing technology, and fiber optics in sensors and control systems.